2015
DOI: 10.1038/srep10704
|View full text |Cite
|
Sign up to set email alerts
|

Fatal H5N6 Avian Influenza Virus Infection in a Domestic Cat and Wild Birds in China

Abstract: H5N6 avian influenza viruses (AIVs) may pose a potential human risk as suggested by the first documented naturally-acquired human H5N6 virus infection in 2014. Here, we report the first cases of fatal H5N6 avian influenza virus (AIV) infection in a domestic cat and wild birds. These cases followed human H5N6 infections in China and preceded an H5N6 outbreak in chickens. The extensive migration routes of wild birds may contribute to the geographic spread of H5N6 AIVs and pose a risk to humans and susceptible do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 8 publications
0
59
0
1
Order By: Relevance
“…By 2014, H5N2 and H5N8 viruses had spread by migratory birds to poultry in multiple continents (10). Although H5N6 virus is still limited in China and Laos (6-9, 13), reports show that H5N6 virus is gradually becoming more prevalent in poultry than H5N1 virus in China (9). It is a concern that wild birds would spread the H5N6 virus to distant places to become the next potential candidate of global dissemination after H5N2 and H5N8 viruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By 2014, H5N2 and H5N8 viruses had spread by migratory birds to poultry in multiple continents (10). Although H5N6 virus is still limited in China and Laos (6-9, 13), reports show that H5N6 virus is gradually becoming more prevalent in poultry than H5N1 virus in China (9). It is a concern that wild birds would spread the H5N6 virus to distant places to become the next potential candidate of global dissemination after H5N2 and H5N8 viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Avian H5N6 influenza virus was first isolated from mallards in North America in 1975 (5). In China, H5N6 virus first emerged in 2010 and has since been extensively circulating in both domestic and wild birds (6)(7)(8)(9). Recent surveillance data from the Ministry of Agriculture of China indicate that H5N6 viruses have become enzootic in domestic poultry.…”
mentioning
confidence: 99%
“…All H5 subtypes in LPMs possessed a run of polybasic amino acid residues at the HA1-HA2 cleavage site (PLRERRRK R/GL for H5N6, PQIEGRRRKR/GL for H5N2 and PQRER RRKR/GL for H5N1), which is the signature of highly pathogenic H5N1 influenza A virus (Stieneke-Gröber et al, 1992). 2015; Yang et al, 2015;Yu et al, 2015b). All H5N6 viruses identified in this study fell into the 2.3.4.4 clade (Figs 2 and S1a).…”
Section: Evolutionary History Of Aivsmentioning
confidence: 99%
“…In addition to the H5N1 subtype, the novel reassortants H5N2, H5N6 and H5N8 viruses (H5Nx) also have attracted a lot of attention. Studies have shown that viruses isolated in China show low to high pathogenicity in chickens; mild to high virulence in ducks; and moderate to highly pathogenicity in mammals (virulence differs among different virus strains) [63,69,[131][132][133][134][135] (Table 1). However, viruses isolated from other countries, such as South Korea, the USA and some European countries, exhibited low to moderate virulence in mammals [148,151,156,157] (Table 1).…”
Section: Pathogenicity Of Haivsmentioning
confidence: 99%
“…Zhang et al have shown that most of the H9N2 viruses isolated before 2000 fail to be transmitted efficiently to aerosol contact groups of chickens [66] . However, a number of viruses isolated from 2001 onwards not only replicate efficiently in the infected chickens but also transmit [56] Low to high [120,123,136,137] Low to high [56,136] Variability of virulence in migratory waterfowl [138] ; Lethal to quails [139,140] , budgerigars [140] , geese [141] , cats [8,142] , tigers [9,11] and dogs [10] ; Nonlethal to guineapigs [143] , pigs [140,144] and pigeons [121,145] H5N2 Low to high [63] ; High [146,147] Low to high [63] Low to moderate [148] ; Moderate [146] Nonlethal to dogs [149] H5N5 High [62,131] Mild to moderate [131] Moderate [62,131] / H5N6 High [133,134,150] / Low [151] ; Moderate [133] Lethal to cats and swan geese [132] ; Lethal to human [152] H5N8 High [131] ; Low [153] Moderate …”
Section: Transmission Of the H9n2 Aivsmentioning
confidence: 99%